1996
DOI: 10.1042/bj3140805
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin stimulates wortmannin-inhibitable phosphoinositide 3-kinase and membrane blebbing in CHRF-288 cells

Abstract: We have investigated thrombin-stimulated morphological changes and the activation of phosphoinositide 3-kinase (PI 3-K), as manifested by the accumulation of PtdIns(3,4)P2 and PtdIns(3,4,5)P3 (labelled with 32P or myo-[3H]inositol), in CHRF-288 cells, a leukaemic cell line derived from a platelet progenitor cell. We report that these cells, when exposed to thrombin or SFLLRN (the peptide Ser-Phe-Leu-Leu-Arg-Asn, a thrombin-receptor ligand) rapidly change shape, forming membrane ‘blebs’, detectable by different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Although our experiments do not distinguish between inhibition of PtdIns 3/4-kinases, we note that low levels of LY and WT (predicted from experiments on mammalian cells to block PtdIns 3-kinase but not PtdIns 4-kinase activity) are sufficient to block cytokinesis. Further support for PtdIns 3-kinase involvement is that after washout of either LY or WT there is dramatic cellular blebbing, similar to previously reported effects of activation of PtdIns 3-kinase (Vemuri et al, 1996).…”
Section: Multiple Ptdins Steps Influence Cytokinesissupporting
confidence: 68%
“…Although our experiments do not distinguish between inhibition of PtdIns 3/4-kinases, we note that low levels of LY and WT (predicted from experiments on mammalian cells to block PtdIns 3-kinase but not PtdIns 4-kinase activity) are sufficient to block cytokinesis. Further support for PtdIns 3-kinase involvement is that after washout of either LY or WT there is dramatic cellular blebbing, similar to previously reported effects of activation of PtdIns 3-kinase (Vemuri et al, 1996).…”
Section: Multiple Ptdins Steps Influence Cytokinesissupporting
confidence: 68%
“…Membrane blebbing also occurs as a consequence of thrombin stimulation in a wortmannin-sensitive manner in CHRF-288 cells (60). Because this effect was shown to act though phosphoinositide 3-kinase, we also tested the effects of wortmannin on SP-induced blebbing and found that it occurred in a phosphatidylinositol 3-kinase-independent manner (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that staurosporine may antagonize either ROCK or MLCK kinase activity. Membrane blebbing in response to thrombin receptor activation has also been associated with phosphoinositide 3-kinase (Vemuri et al, 1996).…”
Section: Discussionmentioning
confidence: 99%